Association between triglyceride-glucose index and activities of daily living disability among middle-aged and older patients with arthritis: longitudinal evidence from CHARLS - Ma, Liang; Mu, Yu-long; Liu, Zhuo-ming; Jiang, Shu-wei; Li, De-qiang (Frontiers in Medicine, 2025)
ObjectiveTo investigate the longitudinal association between the triglyceride-glucose (TyG) index and activities of daily living (ADL) disability in middle-aged and older adults with arthritis.MethodsWe analyzed data from the China Health and Retirement Longitudinal Study (CHARLS, 2015–2018), including 2,695 arthritis patients without baseline ADL disability. The TyG index was calculated as ln [fasting triglycerides (mg/dL) × fasting plasma glucose (mg/dL)/2]. ADL disability was defined as a score of ≥ 1 based on combined basic and instrumental ADL assessments. Multivariable Cox proportional hazards models were employed to analyze the association, with potential non-linear relationship explored using restricted cubic splines.ResultsOver a median follow-up of 35.98 months, 369 participants (13.69%) developed ADL disability. In fully adjusted models, each 1-unit increase in TyG index was associated with a 26% elevated risk of ADL disability (Hazard ratio [HR] = 1.26, 95% confidence interval [CI]: 1.05–1.51). Compared to the Low TyG, the moderate-High TyG and High TyG showed 40% (HR = 1.40, 95%CI: 1.02–1.92) and 64% (HR = 1.64, 95%CI: 1.18–2.29) increased risks, respectively (P-trend = 0.003). Restricted cubic spline analysis revealed that higher levels of TyG index (> 8.65) were associated with progressively higher ADL disability risk. Subgroup analyses indicated greater risk amplification in younger patients (< 60 years: High TyG vs. Low TyG HR = 1.98, 95%CI: 1.09–3.60). Sensitivity analyses showed that these associations remained statistically significant across multiple analytic approaches, including analyses of unimputed data (HR = 1.43, 95% CI: 1.10–1.86), weighted Cox models, directed acyclic graph-based minimum adequate adjustment, and competing-risks models.ConclusionElevated TyG index shows a significant independent association with ADL disability in arthritis patients. These findings provide mechanistic support for the “metabolic-joint axis” hypothesis and suggest that metabolic monitoring might facilitate identification of individuals with elevated risk profiles of functional decline. The TyG index may serve as an economical risk assessment tool in primary care settings.